2003
DOI: 10.1385/ir:27:1:53
|View full text |Cite
|
Sign up to set email alerts
|

Immunity to Liver Stage Malaria: Considerations for Vaccine Design

Abstract: Malaria is the world's deadliest parasitic disease and effective control measures are a public health priority. Most deaths in humans from malaria are caused by one species of the protozoa, Plasmodium falciparum. An efficacious and cost-effective vaccine against this parasite is considered a holy grail of modern molecular medicine. A vaccine that targets liver stage parasites would prevent infection from reaching the blood and causing clinical disease. Among known P. falciparum antigens, liver stage antigen-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 106 publications
(130 reference statements)
0
8
0
Order By: Relevance
“…Sera and cells from these individuals recognize proteins expressed on the sporozoites and the parasite liver forms [5][6][7][8][9] that have been incriminated in this protection and therefore have been proposed as malaria vaccine candidates. 10,11 Among them, the circumsporozoite (CS) protein that is abundantly expressed on the sporozoite surface has been shown to be involved in the process of parasite invasion to the hepatocyte 12,13 and its immunological blockage prevents the development of malaria infection. 6,7,14 The RTS-S vaccine based on a construct of the Plasmodium falciparum CS protein and the S antigen of human hepatitis B virus has proven to be immunogenic and partially protective in phase II studies conducted with human malaria-naive volunteers [15][16][17][18] and in adults and children from malaria-endemic areas of Africa.…”
Section: Introductionmentioning
confidence: 99%
“…Sera and cells from these individuals recognize proteins expressed on the sporozoites and the parasite liver forms [5][6][7][8][9] that have been incriminated in this protection and therefore have been proposed as malaria vaccine candidates. 10,11 Among them, the circumsporozoite (CS) protein that is abundantly expressed on the sporozoite surface has been shown to be involved in the process of parasite invasion to the hepatocyte 12,13 and its immunological blockage prevents the development of malaria infection. 6,7,14 The RTS-S vaccine based on a construct of the Plasmodium falciparum CS protein and the S antigen of human hepatitis B virus has proven to be immunogenic and partially protective in phase II studies conducted with human malaria-naive volunteers [15][16][17][18] and in adults and children from malaria-endemic areas of Africa.…”
Section: Introductionmentioning
confidence: 99%
“…One such antigen that has been studied extensively is the immunodominant circumsporozoite (CS) protein that is the major surface protein of sporozoites, the hepatocyte-invasive stage of the Plasmodium life cycle [12]. Passive transfer of a CTL clone recognizing P .…”
Section: Introductionmentioning
confidence: 99%
“…During this incubation period, the parasites express liver stagespecific antigens, including LSA-1 and LSA-3. These preerythrocyte antigens evoked specific humoral and cellular immune responses in the hosts and have been recognized as candidates for vaccine (Aidoo et al, 2000;Daubersies et al, 2000;Joshi et al, 2000;Kurtis et al, 2001;Perlaza et al, 2001;Sauzet et al, 2001;Taylor-Robinson, 2003). In this consideration, the liver stage-specific antigen could also be a good diagnostic candidate for early diagnosis of malaria.…”
Section: Discussionmentioning
confidence: 99%
“…Specific humoral, cellular, and cytokine immune responses to LSA-1 and LSA-3 are well documented, with epitopes identified that correlate with the antibody production, proliferative T-cell responses, or cytokine induction (Aidoo et al, 2000;Joshi et al, 2000;Perlaza et al, 2001). Both preerythrocyte antigens have been considered to be vaccine candidates against P. falciparum due to their antigenic and protection-inducing immunogenic properties Kurtis et al, 2001;Sauzet et al, 2001;Taylor-Robinson, 2003). In the present study, we evaluated the usefulness of P. falciparum LSA-3 as a serodiagnostic antigen for a more rapid diagnosis of falciparum malaria than using the currently available diagnostic tools.…”
Section: Usefulness Of the Recombinant Liver Stage Antigen-3 For An Ementioning
confidence: 99%